2007
DOI: 10.1186/1471-230x-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral therapy in neonatal cholestatic cytomegalovirus hepatitis

Abstract: Background: Neonatal hepatitis refers to a heterogeneous group of disorders, caused by many factors including cytomegalovirus infection, revealing similar morphologic changes in the liver of an infant less than 3 months of age. Approximately 40% of cholestasis in infants is due to neonatal hepatitis. It may cause latent or acute cholestatic or chronic hepatitis, including cirrhosis in immunocompetant infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
(18 reference statements)
1
20
1
3
Order By: Relevance
“…Previous studies have reported that transaminases reached the highest levels (<200 U) during the second or third week of infection, decreasing to normal values by the fifth week18). In our study, transaminases increased up to 1,838 IU/L, and most patients showed a significant decrease in transaminases to normal values at 4 months in the follow-up group.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have reported that transaminases reached the highest levels (<200 U) during the second or third week of infection, decreasing to normal values by the fifth week18). In our study, transaminases increased up to 1,838 IU/L, and most patients showed a significant decrease in transaminases to normal values at 4 months in the follow-up group.…”
Section: Discussionsupporting
confidence: 56%
“…Another limitation is that our results were not validated by histopathological findings of the liver, because we did not acquire liver biopsies from the patients. In the histopathological examination of liver, the presence of cytomegalic cells and inclusion bodies refers to the intense immune activation against viral attack18). Hence, the immune activation status after CMV infection was not confirmed in this study either.…”
Section: Discussionmentioning
confidence: 64%
“…Ozkan et al [12] found inclusion bodies in one out of seven infants with neonatal CMV hepatitis. Moreover, despite the documentation of a CMV infection on the initial assessment, we proceeded with exclusion of BA by IOC.…”
Section: Discussionmentioning
confidence: 98%
“…There are reports of effective ganciclovir treatment of acute CMV hepatitis in immunocompetent children [29,30]. Also, biochemical, serological, virological improvements have been reported in cases of neonatal cytomegalovirus cholestatic hepatitis treated with ganciclovir [31]. Thus, administration of ganciclovir can be considered in CMV hepatitis patients with severe jaundice, coagulopathy or severe ALT elevation; however, specific levels of bilirubin, ALT, PT (INR) have not been established.…”
Section: Discussionmentioning
confidence: 99%